Innovation in traditional handicraft companies towards sustainable development. A systematic literature review - Shafi, Mohsin; Szopik-Depczyńska, Katarzyna; Cheba, Katarzyna; Ciliberto, Cristina; Depczyński, Radosław; Ioppolo, Giuseppe (Technological and Economic Development of Economy, 2022)
Despite being rich in cultural heritage, traditional handicrafts require innovation to achieve competitiveness. This study addresses the understanding of innovation in traditional handicrafts for sustainable development. The paper emphasizes the importance and potential advantages of innovation and its synergistic effect with cultural traditions leading to sustainable development. Apart of the explanation of most important issues regarding this topic, publications containing the following keywords selected for the study were identified in the WOS database. A total of 500 different publications from 1975 to 2021 were identified. The database was used for text-mining analyses. The clustering method (data mining) was used. The systematic literature review was carried out with the use of VOSviewer software. This tool was used to identify and analyse clusters and dominant research areas and to identify potential new research directions. This has never been done by any author before. We show that future studies should focus on the issue of measuring incremental innovation in cultural creative industries, especially handicraft since this topic is not enough analysed in the literature. The findings can help academics and practitioners to improve the knowledge about the topic and concentrate on identified priority areas to fulfil the assumptions of sustainable development.First published online 21 September 2022